Avifaunal Diversity of Khata Corridor Forest - Chaudhari, Umesh Kumar; Kafle, Gandhiv; Baral, Hem Sagar (Journal of Wetlands Ecology, 2009)
The study was made to assess the species diversity of avians, habitat type, their presence/absence in the different habitats and to produce a distribution map of globally threatened species in Khata Corridor forest of Bardia district. Species discovery curve and richness curve was produced through McKinnon list method in which each list contains 15-species. Habitat type was distinguished by modified DAFOR scale. Riverine sissoo-khair forest, Moist-mixed forest, and Riverine grassland were found to be prominent habitat type in the intensive study area. Distribution map of threatened species was assembled through Arc View 3.2a. Shannon’s Index of Diversity (H = 3.114) and species evenness (0.629) indicates the high species diversity of avians in Khata corridor forest. Further study is essential to incorporate remaining part of the forest and to survey winter birds. Key words: Avifauna, corridor, species diversity, habitat DOI: 10.3126/jowe.v2i1.1857 Journal of Wetlands Ecology, (2009) vol. 2, pp 48-56